The Effectiveness of Online EMDR 2.0 Group Protocol on Posttraumatic Stress Disorder Symptoms, Depression, Anxiety, and Stress in Individuals Who Have Experienced a Traffic Accident: A Preliminary Study - Yaşar, A.B.; Kavakçı, Ö.; Çiftçi, Z.Z.; Tunca, G.A.; Uygun, E.; Gündoğmuş, İ.; Kubilay, D. (Springer Publishing Company, 2023)
Introduction: As an innovative procedure, eye movement desensitization and reprocessing (EMDR) 2.0, which is based on standard EMDR, draws attention with its promising results. The adaptation of EMDR 2.0 to groups will be a significant contribution to the psychology literature. Considering the effectiveness of EMDR 2.0 on individual applications, this is a preliminary study that aims to explore the role of EMDR 2.0 on groups by developing the EMDR 2.0 group protocol (EMDR 2.0 GP). Methods: In this pilot study, EMDR 2.0 GP is applied to a group of seven participants who had been exposed to a traffic incident. The role of EMDR 2.0 GP (three sessions; 3.5 hours in total) on posttraumatic stress disorder (PTSD) symptoms, depression, anxiety, and stress was measured. The Impact of Event Scale—Revised and the Depression-Anxiety-Stress Scale-21 (DASS-21) were used to assess these symptoms at pretreatment, one-week posttreatment, and one-month posttreatment. Results: The participants (mean age = 47.14 ± 9.65) with a traffic accident experience (mean of the time elapsed = 88.57 ± 38.24 months) received EMDR 2.0 GP. Results showed that the EMDR 2.0 group had significantly lower depression (?² [2, n = 7] = 9.364, p =.009, Kendall’s W =.668) and stress (?² [2, n = 7] = 8.667, p =.013, Kendall’s W =.619) on the subscales of DASS-21 and lower intrusions (?² [2, n = 7] = 6.333, p =.042, Kendall’s W =.452), avoidance (?² [2, n = 7] = 7.280, p =.026, Kendall’s W =.520), and hyperarousal (?² [2, n = 7]) = 10.800, p =.005, Kendall’s W =.771) at posttreatment. Conclusion: The pilot study of EMDR 2.0 GP indicated that this newly developed protocol that was first applied to the group may be effective in reducing depression, stress, and PTSD symptoms among a nonclinical sample. This pilot study supports future randomized controlled EMDR GP applications. © 2023 EMDR International Association.
Keywords: Emdr; Emdr 2.0; Emdr 2.0 Group; Online Emdr; Telehealth Intervention; Trauma